(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate the association of lymph node retrieval, lymph node ratio (LNR)and various other prognostic factors in the management of colorectal cancer (CRC). Study Design: A retrospective and longitudinal study. Place and Duration of Study: This study was conducted at the Department of General Surgery Khalifa Gul Nawaz (KGN)MTI Bannu between July 2019 and January 2020. Materials and Methods: This study was conducted on the data of 450 consecutive patients with colorectal cancer (CRC), admitted to the Department of General surgery KGN MTI Bannu between Jan 2010 and Dec 2014 and who underwent curative resection for colorectal cancer. The data was collected from the clinical charts, computer record and the pathological reports and were reviewed retrospectively and longitudinally for various prognostic factors in the management of CRC. Follow up period was 5 years. The data were fed to the computer for analysis and calculation of rates, percentages, means and median of variables. Comparisons between variables were assessed for significance by using Pearson chi-squar (x2) test and Fischer exact test, with the threshold for significance the p<0.05. Kaplan-Meier curves were used to calculate and depict the overall survival in different groups of patients. Results: A total of 450 patients with colorectal cancer were analyzed. For stage1 and stage11 or node negative disease, the 5yr survival was 65-70%, declining to 50% for patients with stage 111 or node positive disease. For Duke stages B and C, there was a significant difference in the overall survival (OS)in patients with <12 versus >12 lymph nodes (LNs) retrieved. There was a statistically significant difference in the overall survival (OS), disease free survival (DFS) and recurrence rates in patients with different number of lymph nodes retrieved, the number of lymph nodes with metastases and lymph nodes ratios (LNRs). Histological subtypes, the surgeon, and the pathologist also played a significant prognostic role in the management of CRC. Conclusion: Retrieval of >12 lymph nodes, thorough evaluation of lymph nodes and decreased lymph nodes ratio have a significant effect on the long term survival and recurrence in the CRC patients.